A bio-indicator assessment towards the rehabilitation of the Stiebeuel River, Franschhoek, South Africa - Cameron, Kieran (Humanities: Academic Administration, 2019)
Increased urbanization coupled with the effects of urban stream syndrome and urban informal settlements are degrading rivers and causing a decline in habitat integrity and the delivery of ecosystem services. There is a need to implement river restoration programmes to alleviate the negative impacts on stream ecosystems. This study aimed to determine the ability of a contaminated urban stream, draining Langrug, an informal settlement, to enrich the biodiversity of species and organisms, following a rehabilitation intervention. It was investigated how nature, in the form of biodiversity of diatoms and macro-invertebrates, were observed in the Stiebeuel River when a range of habitats were created and restored through the replanting of indigenous vegetation within the Stiebeuel River channel. The focus of the study is on understanding the value of different types of bio-assessment and water quality methodologies for informing the rehabilitation of a river system. It also illustrates how a combination of methods as opposed to a single method is able to inform the ecological integrity of habitat restoration.The results showed the current physical and biological condition of the Stiebeuel River to be heavily degraded, critically modified, with poor river health and an ecological category between D and E/F. The low DO levels and high EC levels are correlated to low SPI scores and high %PT scores, which infers that there is a significant amount of organic pollution and nutrients in the wastewater discharges from Langrug, informal settlement. The miniSASS scores link to the SPI scores, such that the low sensitivity and low SPI scores are attributed to the highly polluted water quality dictating the abundance of pollutant tolerance species. The inflow of highly polluted water from Langrug, informal settlement is responsible for driving the distribution of species in the Stiebeuel River. This highly contaminated water as a result restricted the success of the habitat intervention to enrich biological diversity and improve the ecological status of the Stiebeuel River. The results from the bio-assessment and water quality monitoring overlap and confirms the link between the three monitoring methods